Exploring Talim's forest a community-based management approach to forest conservation and livelihoods on Talim Island, Rizal - Eden, Fara Marie Ina B.; Fernandez, Maria Vio Bianca C. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Forests play a significant role in the lives of millions of people around the world. They
contribute a wide range of ecosystem services and benefits to many individuals and
groups of people, such as the social and economic well-being of the communities.
Furthermore, the forest ecosystem services provide a wide variety of products and opportunities to these growing populations. Forest-dependent communities, or people
who live within or adjacent to the forests, usually depend on forests and forestlands for
their income and subsistence, maintaining their basic necessities and livelihoods. In
particular, the mountainous forest island of Talim located at the center of Laguna Lake,
is characterized by natural features and vegetation, including non-timber forest
resources such as bamboo, which is a significant source of income and livelihood to
the local communities residing within the area. However, existing literature has
reported a decline in forest resources and some reports have observed land
degradation as a result of population growth and increased resource exploitation. For
this reason, the study aims to identify the current livelihood practices and resource
management related to the forests, and investigate the possible exploitive activities by
the people and communities in the island. In order to achieve its goal, the study will
explore and analyze the community-based management approach in protecting the
forests and their natural resources, while ensuring the community welfare in the Talim
Island. Moreover, this study shall demonstrate the importance of collaborative and
participatory approach in the implementation of sustainable forest management
practices and enhancement of the local livelihoods of the communities in Talim Island,
Rizal.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Forests -- Conservation -- Talim Island (Rizal); Community forests -- Talim Island (Rizal); Forest products -- Talim Island (Rizal); Non-timber forest products -- Talim Island (Rizal); Forest management -- Talim Island (Rizal)